Morphological variation in the postabdomen of Camptocercus dadayi Stingelin, 1913 (Cladocera: Anomopoda: Chydoridae) - Andrade, Daniel Da Silva; Sousa, Francisco Diogo Rocha; Elmoor-Loureiro, Lourdes Maria Abdu; Reinés, Juan Manuel Fuentes; Mugnai, Riccardo (Zootaxa, 2025)
We investigated the morphological variations of Camptocercus dadayi Stingelin, 1913 in different populations across South America (Argentina, Brazil, Chile, and Colombia) under optical microscope. Significant variations were observed in the morphology of the postabdomen, especially in the patterns of the marginal denticles, lateral fascicles and terminal claw. The variations follow a geographic pattern throughout South America. These variations suggest morphologic diversity in the species, highlighting the importance of variation studies for the accurate identification and delimitation of species within Camptocercus.